2010
DOI: 10.1007/s12160-010-9220-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the PREMIER Interventions on Health-Related Quality of Life

Abstract: Background Health-related quality of life (HRQOL) is an important aspect of well-being that may improve with health behavior interventions. However, health behavior change is difficult with pressure to maintain status quo. Purpose This report examines the effects of two lifestyle interventions and an advice-only condition on HRQOL. Effects of meeting behavioral goals and weight loss also were examined. Methods Participants were 295 men and 467 women (34% African American) with pre-hypertension or stage 1 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…The size of change attributable to the intervention was smaller than is typically considered clinically significant, 44,45 but may nonetheless be important at the population level. 47 Previous studies that found larger effects were focused on overweight and obese participants. 414,17,18 and individuals with pre-existing coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…The size of change attributable to the intervention was smaller than is typically considered clinically significant, 44,45 but may nonetheless be important at the population level. 47 Previous studies that found larger effects were focused on overweight and obese participants. 414,17,18 and individuals with pre-existing coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Of those studies that exist, the majority have (i) investigated the effect of FV on psychological well-being as a secondary outcome and (ii) investigated the effect of FV modification in conjunction with other dietary or lifestyle changes. Despite this, four dietary interventions have focused more specifically, or have carried out additional analysis, on FV and psychological health (92)(93)(94)(95) . The majority of these have reported heterogeneous findings (92,93,95) .…”
Section: Experimental Evidencementioning
confidence: 99%
“…Despite this, four dietary interventions have focused more specifically, or have carried out additional analysis, on FV and psychological health (92)(93)(94)(95) . The majority of these have reported heterogeneous findings (92,93,95) . For example, Plaisted et al (92) found that although an FV-rich diet was associated with improved vitality in hypertensive participants over 11 weeks, there were no significant differences when compared with an FV-rich, low-fat dairy diet group or a control group.…”
Section: Experimental Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In more recent behavioral weight loss trials (the Diabetes Prevention Program [DPP] [19], Look AHEAD [20], and PREMIER [21]), physical HRQOL improved more in the active intervention arms than in the control arms, with no significant between-arm differences in mental HRQOL change, and a small advantage for the active intervention arm in improved depression symptoms.…”
Section: Introductionmentioning
confidence: 99%